The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jtxs.12538
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear friction dynamics in the cognitive process of food textures: Thickness of polysaccharide solution

Abstract: "Thickness" is one of the descriptors of texture in liquid and semisolid foods. In this study, friction in thickener aqueous solutions was evaluated, using a biomimetic friction evaluation system, to show the correlation between friction data and sensory thickness and the recognition mechanism of this sensation during the process of eating. This system can measure friction forces under sinusoidal movement on fractal agar gel, which mimics the morphology and physical properties of the tongue. We found that an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Although the thickness of the upper agar gel does not significantly affect the friction force or profile, the normalized delay time (δ), which is the normalized time lag in the friction force response to the contact probe’s movement, increases linearly with the thickness of the gel . In addition, we showed the correlation between the friction data of thickener aqueous solutions and the sensory thickness and the recognition mechanism of this sensation during the process of eating, using a biomimetic friction evaluation system . “Thickness” is one of the descriptors of the texture in liquid and semisolid foods.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Although the thickness of the upper agar gel does not significantly affect the friction force or profile, the normalized delay time (δ), which is the normalized time lag in the friction force response to the contact probe’s movement, increases linearly with the thickness of the gel . In addition, we showed the correlation between the friction data of thickener aqueous solutions and the sensory thickness and the recognition mechanism of this sensation during the process of eating, using a biomimetic friction evaluation system . “Thickness” is one of the descriptors of the texture in liquid and semisolid foods.…”
Section: Introductionmentioning
confidence: 84%
“…The friction force between two agar gel substrates in the emulsions was assessed using a sinusoidal motion friction evaluation system (Figure ). The sinusoidal motion was achieved through the Scotch yoke mechanism. The adopted evaluation method is described elsewhere . The sliding velocity ( V ) under the sinusoidal movement was calculated using the stroke length ( A ), angular velocity (ω), and time ( T ), based on eq In the present investigation, the friction conditions were as follows: A = ±14.5 mm; ω = 2.1 rad s –1 ; sampling interval = 1 ms; and normal force ( W ) = 0.39 N. In addition, the maximum sliding velocity ( V max ) and the average sliding velocity ( V ave ) for the angular velocity were 30 and 20 mm s –1 (2.1 rad s –1 ), respectively.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found that the characteristic friction stimulus with high acceleration is one of the cues to distinguish water from thickener aqueous solution [9, 10]. We also evaluated the friction dynamics on fractal agar gels, which mimic the shape and wettability of the tongue surface, and found that the friction profiles vary with the surface shape, vertical load, friction velocity and substance [15–18]. Asanuma et al found that the cosmetic sponge feels highly slippery when the friction force is low [19].…”
Section: Introductionmentioning
confidence: 99%